Taxonomia do gênero Siphonops Wagler, 1828 (Gymnophiona: Siphonopidae) presente nos brejos-de-altitude do Ceará - Ramos, Antônio Rafael Lima (2022)
The caecilians (Gymnophiona) constitute the least diverse group among modern amphibians. Part of this is due to the fossorial habit, which causes undersample of these organisms in scientific collections and also morphological and anatomical conservatism. The family Siphonopidae comprises five genera of Neotropical cecilians. The type genus, Siphonops, currently comprises four species (S. annulatus, S. hardyi, S. leucoderus, and S. paulensis). In the state of Ceará, northeastern Brazil, the genus is probably represented by a taxon not yet well defined, named in different forms in herpetological surveys (S. annulatus, S. paulensis and S. aff. paulensis), with most records occurring in humid forest enclaves, regions within the Caatinga domain that represent isolated fragments of the Atlantic Forest and Amazon, serving as refuges for relict fauna and flora. Using integrative taxonomy, we used different lines of evidence (morphological and molecular) to reassess the taxonomic status of these populations. Our results corroborate the existence of a new phenotypically cryptic species. Siphonops sp. nov. differs from the congeneric species by having a medium-large size and greater variation in the number of primary rings. The sharing of a phylogenetic history with S. annulatus can support the hypothesis that in the past Amazon and Atlantic Forest were biogeographically interconnected. Our hypothesis of Siphonops sp. nov. it is elaborated in the light of the unified concept of species and reinforces the importance of integrating different sources of data for the delimitation of species.